A two-dimensional analysis of anisotropic vibrating beams - Cortínez, Víctor Hugo (2001)
This paper deals with the formulation of a mathematical model for analyzing the dynamics of Beams made with anisotropic materials. The governing equations are solved by means of the finite element method. Some numerical examples are given to show the effect of the anisotropy on the natural frequencies for several boundary conditions.